Viral vector-based transient expression systems for plant biotechnology research at PUIs - Wang, Kevin; Hall, Kylie; Tackett, Kylie; Jordan, Holly; Hall, Gabriella; Campbell, Peyton (Frontiers in Education, 2025)
Traditional stable genetic transformation in plant biotechnology remains largely inaccessible at many Primarily Undergraduate Institution (PUIs) due to high costs, long timelines, and specialized facility demands. Viral vector-based transient expression systems offer an efficient and accessible alternative method that enables meaningful undergraduate research within a single academic term. These systems utilize plant virus-derived vectors (e.g., TMV or Geminivirus) to transiently express target genes, producing detectable recombinant proteins within 3–7 days. Requiring only basic lab tools, they align well with Course-based Undergraduate Research Experiences (CUREs), lab courses, and capstone projects. Students gain practical experience in gene cloning, agroinfiltration, protein or metabolite chemical analysis, while faculty benefit from increased research capacity and funding potential. This mini-review highlights the advantages, implementation strategies, and funding opportunities of viral vector-based transient expression systems at PUIs, underscoring their value in expanding access to synthetic biology, plant-based biomanufacturing, and interdisciplinary STEM education.